Late stages in the biosynthesis of ipecac alkaloids - cephaeline, emetine and psychotrine in Alangium lamarckii Thw. (Alangiaceae) - Jain, Sudha; Chaudhary, Paras Nath; Gawade, Vishal B (Scientific World, 2012)
The bioconversion of tyrosine, dopamine, N- desacetylisoipecoside (15) and N- desacetylipecoside (16) into cephaeline (2), emetine (1), and psychotrine (3) into Alangium lamarckii Thw. (Alangiaceae) plant has been studied. Stereospecific incorporation of N- desacetylisoipecoside (15) into 1,2 and 3 has been demonstrated. Further it has been shown that reduction of C1’ – C2’ takes place after O-methylation of psychotrine (3). Feeding results further showed that cephaeline was poorly metabolized in the plants to form psychotrine (3) thus demonstrating that dehydrogenation of C1’ – C2’ does not take place. The efficient incorporation of cephaeline into emetine (1) further showed that O- methylation is the terminal step in the biosynthesis of emetine. Emetine (1) was poorly metabolized by the plants to form cephaeline (2) and psychotrine (3). The experiments thus demonstrated that dehydrogenation and O-demethylation of emetine (1) does not occur to give cephaeline (2) and psychotrine (3). Scientific World, Vol. 10, No. 10, July 2012 p24-28 DOI: http://dx.doi.org/10.3126/sw.v10i10.6857